Антология выдающихся достижений в науке и технике. Часть 28: Портреты легендарных физиков "высоковольтной бригады" УФТИ - Баранов, Михаил Иванович (НТУ "ХПИ", 2015)
Приведен научно-исторический очерк об известных харьковских физиках, входивших в состав знаменитой "высоковольтной бригады" Украинского физико-технического института, первыми в СССР расщепивших искусственно ускоренными в высоковольтном генераторе с электроразрядной трубкой протонами на энергию до 350 кэВ ядро атома лития и достигших в недалеком будущем своих научных академических вершин и новых научно-технических свершений в области ядерной физики и физики высоких энергий.

Description of the basic distinguished scientific achievements of members of «high-voltage brigade» of the Ukrainian Physical-Technical Institute (UPhTI) and future Academicians in area of nuclear physics − Valter A.C., Sinelnikov C.D., Leypunskiy A.I. and Latyshev G.D. Methodology. Scientific approaches at treatment and systematization of physical knowledges. Historical method atresearch of development in Ukraine and Russia of nuclear physics and mastering of intranuclear energy for military and peaceful aims. Results. The basic creative and vital stages, and also prominent scientific results, obtained by the indicated scientists in the area of nuclear physics, physics of high energies and nuclear energy, are resulted in the compressed and systematized way. Some technical descriptions created by these Kharkov physicists of powerful high-voltage electrostatic and linear dynamitrons and protons, and also nuclear reactors fast-neutron are indicated. Originality. Firstly in the area of history of scientific-technological authoritative enough scientist-electro-physicist, which is engaged not alone ten of years by creation of powerful generators of very high voltage and large currents, and also presents a theoretical electrophysics a wide reader a scientifically-historical essay with not popular details about the first in the USSR breaking up the physicists of UPhTI of atomic kernel of lithium by artificially speed-up protons. Firstly the basic distinguished scientific achievements of the considered physicists-nuclear engineers are resulted in the concentrated way. Practical value. Scientific popularization of physical knowledges and achievements of the known compatriots, bringing ina big contribution to development of nuclear physics, physicists of high energies and nuclear energy.
An anthology of the distinguished achievements in science and technique. Part 28: Portraits of legendary physicists of "high-voltage brigade" of UPhTI
Keywords: история науки; физика ядерная; физика высоких энергий; энергетика ядерная; history; nuclear physics; physics of high energies; nuclear energy